Single virus tracking of Ebola virus entry through lipid rafts in living host cells - Cong Jin; Bin Che; Zhengyuan Guo; Chuan Li; Yang Liu; Wei Wu; Shiwen Wang; Dexin Li; Zongqiang Cui; Mifang Liang (Elsevier, 2020)
Ebola virus (EBOV) is one of the most pathogenic viruses in humans which can cause a lethal hemorrhagic fever. Understanding the cellular entry mechanisms of EBOV can promote the development of new therapeutic strategies to control virus replication and spread. It has been known that EBOV virions bind to factors expressed at the host cell surface. Subsequently, the virions are internalized by a macropinocytosis-like process, followed by being trafficked through early and late endosomes. Recent researches indicate that the entry of EBOV into cells requires integrated and functional lipid rafts. Whilst lipid rafts have been hypothesized to play a role in virus entry, there is a current lack of supporting data. One major technical hurdle is the lack of effective approaches for observing viral entry. To provide evidence on the involvement of lipid rafts in the entry process of EBOV, we generated the fluorescently labeled Ebola virus like particles (VLPs), and utilized single-particle tracking (SPT) to visualize the entry of fluorescent Ebola VLPs in live cells and the interaction of Ebola VLPs with lipid rafts. In this study, we demonstrate the compartmentalization of Ebola VLPs in lipid rafts during entry process, and inform the essential function of lipid rafts for the entry of Ebola virus. As such, our study provides evidence to show that the raft integrity is critical for Ebola virus pathogenesis and that lipid rafts can serve as potential targets for the development of novel therapeutic strategies.